Mitochondrial gene expression in trypanosomatids - Procházková, Michaela (Jihočeská univerzita, 2018)
This thesis comprises of diverse projects all focused towards analysis of mitochondrial translation in unicellular parasites. As only two mitochondrially encoded genes are required during the life cycle stage when Trypanosoma brucei resides in the bloodstream of a mammalian host, this protist provides a simplified background in which to study mitochondrial translation termination phase. The leading project utilizes T. brucei to examine mitochondrial translation termination factor TbMrf1 by gene knockout. Subsequently, it is suggested that the peptidyl-tRNA hydrolase TbPth4 is able to abate the TbMrf1 knockout phenotype by its ability to rescue mitoribosomes that become stalled when TbMrf1 is absent. Additionally, modifying methyltransferase of TbMrf1, the TbMTQ1, was characterized. And finally, this work contributed to the development of the protein expression regulation method in Leishmania parasites, a protocol for measurement of proton pumping activity of FoF1 ATPase complex in native mitochondria, and optimization of purification protocol for hydrophobic recombinant proteins.
Mitochondrial gene expression in trypanosomatids
Keywords: Trypanosoma brucei; mitochondrial translation; mitochondrial release factor 1; Mfr1; Pth4; protein MIX; safranine quenching assay; cytosolic release factor; Leishmania; Trypanosoma brucei; mitochondrial translation; mitochondrial release factor 1; Mfr1; Pth4; protein MIX; safranine quenching assay; cytosolic release factor; Leishmania